Mechanical Behavior of Lumbar Spine Functional Units in Response to Cement Augmentation of Vertebra Body - Tabatabaei, Seyed Mohammad; Haghpanahi, Mohammad (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Cement augmentation in vertebrae is used to promote mechanical strength after spinal fracture and recently vertebroplasty gaining popularity as a treatment for patients. The numerical simulation could be helpful to enhance the quality of treatments such as vertebroplasty via exact modeling of the lumbar spine. Materials and Methods: In this study, a three-dimensional finite element model created from CT images of L1-L3. According to clinical observation and recent studies, we consider that L2 augmented with two different volumes in 10 different distributions. Loadings were assumed to be pure momentum which applied in three anatomical directions (axial rotation, flexion, and lateral bending). Results: Our results were validated with experimental data which shows segments range of motion, ligaments forces, and intradiscal pressure had good agreement with our results. Cement augmentation increases max Von Misses stress in L2 cancellous bone and Increment in Cement volume has the same result. Cement augmentation increases L1-L2 intradiscal pressure. Cement augmentation decreases segments range of motion. Finally, Cement augmentation increases total stiffness of model. Conclusion: Taken together, vertebroplasty as a well-known method to treat the fractured vertebra, could be optimized to enhance patients' range of motion and decrease the complication of treatment.